Dental health in Brazilian adults between 1986 and 2010 - Nascimento, Sergio do; Frazao, Paulo; Bousquat, Aylene; Antunes, Jose Leopoldo Ferreira (Revista de Saúde Pública, 2013)
OBJECTIVE: To identify trends in the pattern of dental caries in Brazilian adults. METHODS: Data from epidemiological surveys carried out by the Brazilian Ministry of Health in 1986, 2003 and 2010 were used. Dental caries experience, using the DMFT index (decayed, missing and filled teeth) and dental health, expressed by the FS-T index (filled and sound teeth) related to functional teeth, were compared using random samples of 35 to 44 year old residents of each region of Brazil. The differences in dental health between the years were estimated using the ratio of the index values, by Poisson regression analysis adjusted for age. RESULTS: Reduction in the DMFT index and increase in the FS-T index in all regions in the period between 1986 and 2010. The North, where the worst standards were found in 1986, showed the greatest improvements in terms of functional teeth. CONCLUSIONS: The dental health of Brazilian adults changed for the better. It is plausible that this oral health transition is related to the addition of fluoride to water and to toothpaste as well as increased incorporation of restorative services and improvements in human development due to public policies.